Children of the postwar years: A two-generational multilevel risk assessment of child psychopathology in northern Uganda. (27th November 2015) - Saile, Regina; Ertl, Verena; Neuner, Frank; Catani, Claudia
Abstract: In postconflict settings risk factors at multiple levels of the social ecology, including community, family, and relationship factors, potentially affect children's mental health. In addition, intergenerational risk factors such as guardians' history of childhood family violence, war exposure, and psychopathology may contribute to children's psychopathological symptoms. In this study, we aimed to identify risk constellations that predict child internalizing and externalizing behavior problems, depression, and posttraumatic stress symptoms in the postconflict setting of northern Uganda. In a cross-sectional epidemiological study, 513 second-grade students and their female guardians were interviewed using standardized clinical questionnaires. A higher exposure to traumatic events, more witnessed or experienced violence within the family, and lower child-reported care from female guardians independently predicted psychopathological symptoms in children. While controlling for intergenerational risk factors in female guardians, serial mediation modeling revealed that the effect of trauma exposure on children's psychopathological symptoms was partially mediated by higher exposure to family violence and lower child-perceived care from female guardians. The mediation appeared to be stronger for children's depression symptoms and internalizing and externalizing behavior problems than for posttraumatic stress symptoms. The current findings support the need for targeted interventions at the individual and family system levels that are matched to children's psychopathological symptoms.